CADASIL‐like leukodystrophy and symptomatic cerebral infarction in myotonic dystrophy type 1 - Liu, Bin; Yang, Chun‐Lin; Li, Xiao‐Li; Zhang, Min; Li, Yan‐Bin; Duan, Rui‐Sheng (CNS neuroscience & therapeutics, 2022)
Among these, brain atrophy and the number of incident lacunes are sensitive MRI markers that could predict clinical worsening in CADASIL. 4 Following a study by Kim et al. in 2018, frontal and parieto-occipital lobes, external capsule, and basal ganglia were involved to a lesser extent in DM1 than in CADASIL. The prevalence of stroke was also less common in DM1 than in CADASIL. 5 Ischemic stroke in patients with myotonic dystrophy type 1 is mainly associated with atrial fibrillation and arteriosclerosis. 6 Hypertriglyceridemia, hypertension, and hyperglycemia were very common in DM1 patients, 7 and severe arteriosclerosis was reported in myotonic dystrophy. 8 This patient has a stroke syndrome and neuroimaging findings consistent with arteriosclerosis. DM1 is caused by an unstable expanded CTG repeats in the noncoding regions of DMPK gene. 9 CADASIL is usually caused by NOTCH3 gene mutations, which provide another biomarker for the differentiation between DM1 and CADASIL. 10 TABLE 1 Brain MRI characteristics in patients with DM1 or CADASIL DM1 CADASIL White matter changes Total Common (over 60%) Very common (over 90%) Frontal Common (over 30%) Very common (over 90%) Parieto-occipital Common (over 50%) Very common (over 90%) Anterior temporal Common (approximately one-third) Common (over 50%) External capsule Rare (about 10%) Very common (over 80%) Basal ganglia Very rare Common (over 60%) Stroke Rare (about 10%) Very common (over 70%) Presence of microbleeds Very rare Common (over 60%) Abbreviations: CADASIL, cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy; DM1, myotonic dystrophy type 1.